Locating Potentials for Solidarity Between Marxism and Intersectionality (KULT_online, 2020)
Ashley J. Bohrer presents a compelling and forceful case for thinking about Marxism and intersectionality as distinct traditions that can nonetheless work in concert with one another. After citing the main contentions that exist between these two traditions, Bohrer ambitiously maps – through detailed historical and nuanced theoretical analyses – how seeming incompatibilities and critiques are more often than not erroneous, based on overly simplistic understandings of and miscommunications between sides. She pinpoints the ways in which these two traditions can be mobilized to work towards their shared ultimate aim of overthrowing oppressive and exploitative structures of racism, sexism, classism, and sexual discrimination under capitalism.